Impact of cardiac rehabilitation on ventricular repolarization indexes in patients with rheumatid arthritis - (:unkn) unknown (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2018)
Objective: Abnormalities in ventricular repolarization (VR) parameters have been associated with sudden cardiac death (SCD) in patients with rheumatoid arthritis (RA). The benefits of cardiac rehabilitation (CR) in patients with RA are well recognized. We aimed to assess its impact on VR indexes in patients with RA. Methods: This study included 45 patients with RA (36 female, age 58 +/- 5.5 years) and 50 age- and sex-matched otherwise healthy controls. Baseline electrocardiogram (ECG) recordings were used to compare VR parameters such as maximum and minimum QT intervals, and corrected, and dispersion (QTmax, QTmin, cQTmax, cQTmin, QTd, cQTd, respectively), JT and cJT intervals, Tp-e and cTp-e intervals, and Tp-e/QT and Tp-e/cQT ratios in patients with RA and healthy individuals. The effects of 6-week CR in patients with RA were also evaluated by comparing pre- and post-CR ECG5, exercise tolerance test (MET and VO2max) and RA characteristics (C-reactive protein (CRP), Disease Activity Score 28 (DAS28) and Health Assessment Questionnaire(HAQ)). Results: In comparison with the healthy individuals, the patients with RA had significantly higher cQTmax and QTmin intervals, QTd, cQTd, Tp-e and cTp-e intervals, and Tp-e/QT and Tp-e/cQT ratios. At the end of CR, all VR indexes (p < 005), except QTd, were significantly decreased as did the results for CRP, DAS28, and HAQ (all p < 0.05), and MET and VO2max (p < 0.05 for both) were significantly increased in patients with RA. Conclusions: CR may provide an improvement in the majority of VR indexes which are related with ventricular arrhythmia and SCD in patients with RA. Changes in ETT parameters and RA characteristics may contribute to improvement of several VR indexes such as cQTd, cJT and Tp-e intervals at the end of CR. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Rheumatoid arthritis; Cardiac rehabilitation; Ventricular repolarization indexes; CORRECTED QT INTERVAL; TP-E/QT RATIO; INFLAMMATORY ARTHRITIS; CARDIOVASCULAR-DISEASE; ASSOCIATION; MORTALITY; DEATH; RISK; RECOMMENDATIONS; ARRHYTHMIAS